ANALISIS PROSES BISNIS PADA SEKOLAH MUSIK MENGGUNAKAN ZACHMAN FRAMEWORK - Berliana Glorya Liebe Imbing; Johanes Fernandes Andry (P3M Politeknik Negeri Banjarmasin, 2020)
More and more music school institutions are appearing in various places, there are also many offers that arise based on the excellence and uniqueness of each existing music school. Many school music business processes are primarily looking for as many students who are interested in music, there are also music schools whose main business is teaching techniques and how to play music as well as theories in music. Good marketing that is supported by teaching methods that are suitable for today's children, and the strengths of other music schools will be the customer's priority material and will register themselves as students if what is offered by the music course institution is in accordance with the level of customer interest. Management of a neat and organized music school, many achievements, many students, branches and partners make a Music School Institute a power for prospective customers. The application of SI / IT is needed in every field of the company including music schools. Therefore, this research is expected to provide input to companies to implement IS / IT in accordance with business processes. The results of this study are in the form of proposals for the formation of applications that will be applied in the company's business processes, both the main activities and supporting activities.